Disc Diffusion and ComASP® Cefiderocol Microdilution Panel to Overcome the Challenge of Cefiderocol Susceptibility Testing in Clinical Laboratory Routine - Gabriele Bianco; Matteo Boattini; Sara Comini; Giuliana Banche; Rossana Cavallo; Cristina Costa (MDPI AG, 2023)
Cefiderocol susceptibility testing represents a major challenge for clinical microbiology. Although disc diffusion showed robustness to test cefiderocol susceptibility, large areas of technical uncertainty (ATU) are reported by current EUCAST breakpoints. Herein, we evaluated the in vitro activity of cefiderocol on a collection of 286 difficult-to-treat Gram-negative isolates using disc diffusion and ComASP® cefiderocol microdilution panel. Broth microdilution (BMD) in iron-depleted Mueller-Hinton broth was used as reference method. Following the EUCAST guidelines, disc diffusion allowed to determine cefiderocol susceptibility (susceptible or resistant) in 78.6%, 88.1%, 85.4% and 100% of Enterobacterales, P. aeruginosa, A. baumannii and S. maltophilia isolates tested, respectively. ComASP® cefiderocol panel showed 94% and 84% of overall categorical agreement and essential agreement. Only one very major error and two major errors were observed, for MIC values nearly close to the resistance breakpoint (2 mg/L). Overall, 20.5% of the carbapenemase-producing Enterobacterales that achieved ATU results by the disc diffusion method tested resistant by both ComASP® panel and reference BMD. Conversely, all VIM-producing P. aeruginosa showed MIC values in the susceptible range (≤2 mg/L). Lastly, only six out of seven (85.7%) A. baumannii isolates showing inhibition zones <17 mm tested resistant by both ComASP® panel and the reference BMD suggesting that inhibition zone <17 mm are not unequivocally suggestive of resistance. Our results, although obtained on a limited number of isolates, suggest that the combination of disc diffusion with a ComASP® cefiderocol microdilution panel could be a viable solution to overcome the challenge of cefiderocol susceptibility testing in routine microbiology laboratories.